PERAN INDEPENDENSI, TEKANAN WAKTU, KOMPLEKSITAS TUGAS, DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT - I Dewa Ayu Dian Pratiwi; Ni Nyoman Ayu Suryandari; Anak Agung Putu Gede Bagus Arie Susandya (Universitas Trunojoyo Madura, 2019)
The purpose of this study is to examine the effect of independence, time pressure, task complexity, and auditor experience on audit quality at the Public Accounting Firm in Bali. The population in this study were 13 public accounting firms with 112 auditor respondents. The number of samples used was 55 respondents, with a purposive sampling sample determination method using a minimum criteria of working 2 years on KAP. The data analysis technique used is multiple regression analysis. The results of this study find that auditor independence and experience have a positive effect on audit quality while time pressure and task complexity do not affect audit quality. Auditors are expected to be able to maintain and enhance their independence, which can be used in maintaining relationships with clients and attitudes to make decisions that are not affected by other parties. The increasing auditor experience makes the auditor more professional so that time constraints and task complexity do not decrease audit quality. The higher the auditor's experience in audit activities, the higher the auditor able to produce better audit quality.